Maternity services during COVID-19 Pandemic and lockdown at Provincial Public Hospital in Nepal - Thakur, Murari (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: To assess the hospital delivery pattern during COVID 19 pandemics and lockdown. Methods: This is a retrospective study conducted at Provincial Public Hospital Janakpurdham, Nepal from April to July 2020. Data were collected from hospital record and descriptive analysis performed using MS Excel. Results: Total of 1536 women delivered in three month and caesarean section rate was 16.7% (257/1536). Previous caesarean section was the major contributor (46%) to the overall caesarean section rate. Conclusions: Maternity services were provided during COVID 19 pandemics and Lockdown. Cesarean section rate was near the recommended level. Keywords: Cesarean section, lockdown, pandemic, vaginal deliveries